The Completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: measurement of the BAO and growth rate of structure of the luminous red galaxy sample from the anisotropic power spectrum between redshifts 0.6 and 1.0. Issue 2 (17th August 2020) - Gil-Marín, Héctor; Bautista, Julián E; Paviot, Romain; Vargas-Magaña, Mariana; de la Torre, Sylvain; Fromenteau, Sebastien; Alam, Shadab; Ávila, Santiago; Burtin, Etienne; Chuang, Chia-Hsun; Dawson, Kyle S; Hou, Jiamin; et al.
ABSTRACT: We analyse the clustering of the Sloan Digital Sky Survey IV extended Baryon Oscillation Spectroscopic Survey Data Release 16 luminous red galaxy sample (DR16 eBOSS LRG) in combination with the high redshift tail of the Sloan Digital Sky Survey III Baryon Oscillation Spectroscopic Survey Data Release 12 (DR12 BOSS CMASS). We measure the redshift space distortions (RSD) and also extract the longitudinal and transverse baryonic acoustic oscillation (BAO) scale from the anisotropic power spectrum signal inferred from 377 458 galaxies between redshifts 0.6 and 1.0, with the effective redshift of z eff = 0.698 and effective comoving volume of 2.72 Gpc^3 . After applying reconstruction, we measure the BAO scale and infer D H ( z eff )/ r drag = 19.30 ± 0.56 and D M ( z eff )/ r drag = 17.86 ± 0.37. When we perform an RSD analysis on the pre-reconstructed catalogue on the monopole, quadrupole, and hexadecapole we find, D H ( z eff )/ r drag = 20.18 ± 0.78, D M ( z eff )/ r drag = 17.49 ± 0.52 and fσ 8 ( z eff ) = 0.454 ± 0.046. We combine both sets of results along with the measurements in configuration space and report the following consensus values: D H ( z eff )/ r drag = 19.77 ± 0.47, D M ( z eff )/ r drag = 17.65 ± 0.30 and fσ 8 ( z eff ) = 0.473 ± 0.044, which are in full agreement with the standard ΛCDM and GR predictions. These results represent the most precise measurements within the redshift range 0.6 ≤ z ≤ 1.0 and are the culmination of more than 8 yr of SDSS observations.